2014
DOI: 10.1158/1078-0432.ccr-14-1784
|View full text |Cite
|
Sign up to set email alerts
|

miR-154* and miR-379 in the DLK1-DIO3 MicroRNA Mega-Cluster Regulate Epithelial to Mesenchymal Transition and Bone Metastasis of Prostate Cancer

Abstract: Purpose MicroRNAs in the delta-like 1 homolog - deiodinase, iodothyronine 3 (DLK1-DIO3) cluster have been shown to be critical for embryonic development and epithelial to mesenchymal transition (EMT). DLK1-DIO3 cluster miRNAs are elevated in the serum of metastatic cancer patients. However, the biological functions of these miRNAs in the EMT and metastasis of cancer cells are poorly understood. We previously demonstrated the oncogenic and metastatic role of miR-409-3p/5p, a member of this cluster, in prostate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 42 publications
4
96
0
1
Order By: Relevance
“…vPrevious studies showed that aberrant expression of miR‐379 contributes to cancer development 31, 32, 33. For instance, Khan et al .…”
Section: Introductionmentioning
confidence: 99%
“…vPrevious studies showed that aberrant expression of miR‐379 contributes to cancer development 31, 32, 33. For instance, Khan et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to explore the molecular mechanisms underlying the initiation and development of cervical cancer. A growing amount of evidence has demonstrated that miRNAs are important regulators of various types of biological processes in cancers, including cell proliferation, cell cycle, apoptosis, invasion and migration (24)(25)(26). Furthermore, the abnormal expression of miRNAs is associated with carcinogenesis and progression of cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, miR-154*, miR-379 and miR-409-3p/-5p promote tumourigenesis, EMTand bone metastasis of human prostate cancer. 33 Dicer is a target for miR-103/107, whose expression is associated with metastasis and poor outcome in breast cancer patients. 21 This miRNA family attenuates miRNA biosynthesis by regulating Dicer expression and induces EMT thus enhancing the migratory ability of the cells in vitro and the metastatic dissemination in vivo.…”
Section: Mirnas In Primary Carcinomas Are Potential Predictive Factormentioning
confidence: 99%